2006
DOI: 10.2223/jped.1491
|View full text |Cite
|
Sign up to set email alerts
|

Acellular pertussis vaccine for adolescents

Abstract: Although some questions remain to be clarified, the literature indicates the possibility of solving the "reappearance" of whooping cough (pertussis) with the use of Tdap vaccine. Perhaps the strategy of using a second booster dose in adolescence to replace the double diphtheria and tetanus vaccine should be adopted immediately.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 46 publications
0
5
0
2
Order By: Relevance
“…47,48 The classical vaccine (DPT) has cellular components that can trigger the development of adverse reactions; however, it is recommended in patients with RD, even those on immunosuppressive therapy. 49,50 Four studies including 95 patients and 125 healthy controls show the immunogenicity of the TT or TD vaccines. High antibody concentrations against tetanus (3 studies) and diphtheria (1 study) were found.…”
Section: Diphteria-pertussis-tetanus Vaccinementioning
confidence: 99%
“…47,48 The classical vaccine (DPT) has cellular components that can trigger the development of adverse reactions; however, it is recommended in patients with RD, even those on immunosuppressive therapy. 49,50 Four studies including 95 patients and 125 healthy controls show the immunogenicity of the TT or TD vaccines. High antibody concentrations against tetanus (3 studies) and diphtheria (1 study) were found.…”
Section: Diphteria-pertussis-tetanus Vaccinementioning
confidence: 99%
“…7,60 As for the pertussis fraction, the classical vaccine (DPT) has cellular components capable of triggering the development of adverse reactions, it is also not specifically contraindicated in patients with rheumatic diseases, even those on immunosuppressive therapy (evidence A). 81,82 Patients with an incomplete vaccine schedule should be oriented to complete it normally; in those who completed the schedule, a booster dose in adolescence is recommended, since, along with infants and adults, this age group is one of the most affected by whooping cough (evidence C). 83 Commercial presentations of DTaP with 3 and 5 pertussis components, with similar clinical efficacy, are available (evidence A).…”
Section: Acellular Triple (Dtap/tdap) and Double (Tt/td) Vaccinesmentioning
confidence: 99%
“…Studies in progress have demonstrated that is possible to produce for each 10 or 20 doses of the traditional wP or of the Plow, one dose of the aP vaccine. This vaccine may be used in children who present contraindications for vaccination with wP, or in adolescents 3 , and adults, in which the cellular component is not indicated.…”
Section: Dtp Low -A New Cellular Pertussis Vaccinementioning
confidence: 99%